1989
DOI: 10.1177/074193258901000608
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Assistance Teams: Five Descriptive Studies on 96 Teams

Abstract: School-based teacher support teams are being established by many educational agencies in an effort to assist teachers in more effectively serving students with learning and behavior problems within the general classroom setting. This article addresses questions most frequently asked by educators who are interested in establishing or strengthening school-based teams. Data are summarized from five studies conducted on 96 teams in seven states with respect to intervention goals of teams, team impact on student pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 13 publications
2
97
0
3
Order By: Relevance
“…Selon ce modèle, les services devaient être offerts d'abord au sein même de la classe ordinaire. La documentation, surtout la documentation américaine, révèle qu'il existe plusieurs façons d'offrir les services aux élèves en difficulté d'apprentissage, soit les approches préventives avant la référence (Fuchs, Fuchs, Bahr, Fernstrom et Stecker, 1990;Graden, Casey et Christenson, 1985;Pugach et Johnson, 1989), les équipes de résolution de problèmes (Chalfant et Van Dusen Pysh, 1989), les classes ressources (Wiederholt et Chamberlain, 1989) et les enseignants consultants (Huefner, 1988;West et Idol, 1987). À ces modèles de services s'ajoute la mise sur pied par les écoles de projets, tel le tutorat.…”
Section: Contexte Théoriqueunclassified
“…Selon ce modèle, les services devaient être offerts d'abord au sein même de la classe ordinaire. La documentation, surtout la documentation américaine, révèle qu'il existe plusieurs façons d'offrir les services aux élèves en difficulté d'apprentissage, soit les approches préventives avant la référence (Fuchs, Fuchs, Bahr, Fernstrom et Stecker, 1990;Graden, Casey et Christenson, 1985;Pugach et Johnson, 1989), les équipes de résolution de problèmes (Chalfant et Van Dusen Pysh, 1989), les classes ressources (Wiederholt et Chamberlain, 1989) et les enseignants consultants (Huefner, 1988;West et Idol, 1987). À ces modèles de services s'ajoute la mise sur pied par les écoles de projets, tel le tutorat.…”
Section: Contexte Théoriqueunclassified
“…A review of the research conducted on pre-referral teams has shown that these teams generally have positive outcomes (Chalfant & Pysh, 1989). The schools surveyed reported successful interventions were developed for 70% to almost 90% of their referrals.…”
Section: Pre-referral Intervention Teamsmentioning
confidence: 99%
“…The fourth member is the referring teacher. Other members, such as an administrator or other specialists are sometimes present and such membership varies within and between districts (Chalfant & Pysh, 1989). TATs allow for flexibility in their procedure, with respect to referral forms, and other pre-referral requirements.…”
Section: Pre-referral Team Modelsmentioning
confidence: 99%
See 2 more Smart Citations